Weed Control in Cucurbit Crops (Muskmelon, Cucumber, Squash, and Watermelon) - William M. Stall (EDIS)
Revised! HS-190, a 6-page fact sheet by William M. Stall, describes effective weed management practices for cultivation of cucurbit crops in Florida, and a table of chemical weed controls. Published by the UF Department of Horticultural Sciences, April 2009.